Low performance of a SARS-CoV-2 point-of-care lateral flow immunoassay in symptomatic children during the pandemic - Marcelo Comerlato Scotta; Caroline Nespolo de David; Fernanda Hammes Varela; Ivaine Tais Sauthier Sartor; Márcia Polese-Bonatto; Ingrid Rodrigues Fernandes; Gabriela Oliveira Zavaglia; Charles Francisco Ferreira; Luciane Beatriz Kern; Amanda Paz Santos; João Ronaldo Mafalda Krauzer; Paulo Márcio Pitrez; et al. (Elsevier, 2022)
Objective: to evaluate the accuracy of an antibody point-of-care lateral flow immunoassay (LFI - Wondfo Biotech Co., Guangzhou, China) in a pediatric population. Methods: children and adolescents (2 months to 18 years) with signs and symptoms suggestive of acute SARS-CoV-2 infection were prospectively investigated with nasopharyngeal RT-PCR and LFI at the emergency room. RT-PCR was performed at baseline, and LFI at the same time or scheduled for those with less than 7 days of the clinical picture. Overall accuracy, sensitivity and specificity were assessed, as well as according to the onset of symptoms (7-13 or ≥14 days) at the time of the LFI test. Results: In 175 children included, RT-PCR and LFI were positive in 51 (29.14%) and 36 (20.57%), respectively. The overall sensitivity, specificity, positive and negative predictive value was 70.6% (95%CI 56.2-82.5), 96.8% (95%CI 91.9-99.1), 90.0% (95%CI 77.2-96.0), and 88.9% (95%CI 83.9-92.5), respectively. At 7-13 and ≥14 days after the onset of symptoms, sensitivity was 60.0% (95%CI 26.2-87.8) and 73.2% (95%CI 57.1-85.8) and specificity was 97.9% (95%CI 88.7-99.9) and 96.1% (95%CI 89.0-99.2), respectively. Conclusion: Despite its high specificity, in the present study the sensitivity of LFI in children was lower (around 70%) than most reports in adults. Although a positive result is informative, a negative LFI test cannot rule out COVID-19 in children.